Comparison of growth dynamics in different types of MPS: an attempt to explain the causes - Agnieszka Różdżyńska-Świątkowska; Anna Zielińska; Anna Tylki-Szymańska (Orphanet Journal of Rare Diseases, 2022)
Abstract Background Mucopolysaccharidoses (MPS) are a group of lysosomal storage disorders caused by deficient activity of enzymes responsible for the catabolism of glycosaminoglycans (GAGs), resulting in progressive damage to various tissues and organs. Affected individuals present with skeletal deformities, bone growth impairment, joint stiffness and frequently mental retardation. Results The objective of the study was to summarise over 30 years of observations of the growth dynamics in patients with different types of MPS, performed at the Children’s Memorial Health Institute (CMHI, Warsaw, Poland). A retrospective analysis of anthropometric data collected from 1989 to 2020 was performed for 195 patients with MPS I, MPS II, MPS III, MPS IVA and MPS VI. Mean values for birth body length were statistically significantly greater than in the general population. The mean z-scores for other MPS groups showed that until the 24th month of life, the growth pattern for all patients was similar, and the average z-scores for body height were greater than in reference charts. Afterwards, growth patterns began to differentiate for MPS groups. Conclusions The long-term follow up showed that the growth pattern in patients with all types of mucopolysaccharidoses significantly deviates from the general population. Patients with MPS IVA had the most severe growth impairments compared to other patients in the study group. Neuropathic MPS I and II demonstrated severe growth impairments compared to other patients in this study. Patients with MPS III showed the mildest growth impairments compared to other MPS patients and reached the 3rd percentile last.